Surveying .NZ TLS - Sarten, Lucas (Wellington Faculty of Engineering Symposium, 2023)
The Internet serves as a critical platform for exchanging sensitive information, encompassing businesses such as banks, online stores, and government agencies that routinely transmit and receive personal data over the Web. Ensuring the security of this information is of paramount importance. The security protocols Transport Layer Security (TLS) and its predecessor, Secure Sockets Layer (SSL), play a vital role in securing the modern web. These protocols implement various security measures to ensure the confidentiality, integrity, and authenticity of the data exchanged between web browsers and web servers. Nonetheless, the improper configuration and implementation of TLS/SSL protocols on web servers can introduce security vulnerabilities, potentially compromising user privacy and security. This paper contains the results and conclusions derived from a comprehensive survey of TLS/SSL configurations among websites registered under the .nz top-level domain name. The project evaluated the current TLS/SSL configurations in place and compared them with the latest web security standards and best practices. The findings provide valuable insights into the security posture of websites within the .nz domain, highlighting potential risks, vulnerabilities, and areas of concern. By doing so, we contribute to the broader understanding of web security best practices and help businesses and individuals make informed decisions to enhance the security of sensitive online data.